Side-pumping Nd:YAG solar laser by six Fresnel lenses - Tomás, G. (2021)
To obtain a good compromise between collection efficiency and brightness figure of merit of solar-pumped lasers, a new side-pumping scheme is proposed. Firstly the solar radiations are collected and concentrated by six 700 mm diameter Fresnel lenses. The concentrated solar radiations are subsequently reflected by six plane folding mirrors with 95% reflectivity, into a common focal spot. This allows the concentration of 1740 W solar power with about 6.4 W/mm2 peak solar flux. A secondary concentrator is composed of six aspheric fused silica lenses, positioned around a 40 mm radius fused silica sphere, compressing all the concentrated solar radiation from the six Fresnel lenses into an 8 mm diameter by 9 mm length Nd:YAG single-crystal rod. By positioning the spherical concentrator slightly above the aspherical lenses, a more uniform absorption profile is achieved. Mechanical support with a water cooling system ensures an efficient cooling to the laser medium. Optimal laser parameters are found through ZEMAXTM and LASCADTM numerical analysis software. Only 16% of the solar power is absorbed by Nd:YAG medium. Solar laser power of 42.6 W is numerically calculated, reaching a collection efficiency of 18.5 W/m2. For a 400 mm plane-concave resonance cavity with -5m radius of curvature, M2 x = M2 y = 22 beam quality factors are numerically predicted. A near uniform pump absorption profile can be achieved by increasing the number of Fresnel lens and folding mirrors.